Endoscopic Ultrasound-Guided Fine-Needle Aspiration/Biopsy for Splenic Lesions: A Highly Accurate and Safe Diagnostic Tool - Shaaban HE; Hara K; Haba S; Kuwahara T; Okuno N; Koda H; Urata M; Kondo T; Yamamoto Y; Okasha HH (International Journal of General Medicine, 2025)
Hossam Eldin Shaaban,1 Kazuo Hara,1 Shin Haba,1 Takamichi Kuwahara,1 Nozomi Okuno,1 Hiroki Koda,1 Minako Urata,1 Takashi Kondo,1 Yoshitaro Yamamoto,1 Hussein Hassan Okasha2 1Department of Gastroenterology, Aichi Cancer Center Hospital, Nagoya, Japan; 2Division of Gastroenterology and Hepatology, Department of Internal Medicine, Kasr Al-Aini School of Medicine, Cairo University, Cairo, EgyptCorrespondence: Kazuo Hara, Department of Gastroenterology, Aichi Cancer Center Hospital, 1-1 Kanokoden, Chikusa-ku, Nagoya, Aichi, 464-8681, Japan, Email khara@aichi-cc.jpBackgrounds/Aims: Tissue acquisition from splenic lesions is challenging. The role of endoscopic ultrasound in tissue acquisition for splenic lesions is not fully established due to paucity of published literature. This retrospective study evaluated the effectiveness and safety of endoscopic ultrasound-guided fine-needle aspiration/biopsy for splenic lesions.Methods: Medical records of 18 patients who underwent EUS-FNA/B of splenic lesions at Aichi Cancer Center Hospital, Nagoya, Japan from February 2012 to June 2023 were retrospectively reviewed.Results: Eighteen patients with splenic lesions underwent EUS-FNA/B. Among them, 3 were diagnosed with malignant lesions and 15 with benign lesions. The diagnostic performance of EUS-FNA/B was excellent, with a diagnostic accuracy of 100% (18/18; CI, 81.5– 100%), sensitivity of 100% (3/3; CI, 29.2– 100%), and specificity of 100% (15/15; CI, 78.2– 100%). A total of 34 lesions were sampled across all patients, including 24 splenic lesions, 6 lymph nodes, 2 pancreatic masses, and 2 hepatic focal lesions. Minor complications were observed in three patients: one case of post-procedural bleeding, one of self-limiting abdominal pain, and one case of transient fever that resolved within 24 hours with antibiotics.Conclusion: EUS-FNA/B of splenic lesions demonstrated to be safe and of high diagnostic yield.Keywords: endoscopic ultrasound (EUS), EUS guided fine needle aspiration/biopsy (EUS-FNA/B), splenic lesion, accuracy, safety